Konzepte der Beschaffungslogistik in Katastrophenhilfe und humanitärer Logistik - Hella Abidi; Matthias Klumpp (MA Akademie Verlags- und Druck-Gesellschaft mbH, 2012)
– This research contribution delivers an approach for the materials management in humanitarian logistics with the help of ABC- and XYZ-analysis which is widespread in the industrial praxis. Based on the increase of the number of disasters caused by humans and nature and on the high volume of relief deliveries, logistic systems, infrastructures and information technologies in humanitarian logistics also have to be organized and optimized with the help of commercial and economic methods. This aspect was largely ignored in the past and the area of logistic conceptions and comprehension is based on 10 to 15 year old knowledge.
Keywords: 650; Materialwirtschaft; Logistik; Humanitäre Hilfe; Unternehmensanalyse